Answer:
6 units away from 0.
Step-by-step explanation:
when move to 6 you count the units.
Answer
y = 1(x +1) - 3
Explanation
A quadratic equation of the form y = ax^2 + bx + c
This written in complete the square form provides you with the vertex (either a maximum or minimum point depending on the equation).
This results in y = a(x + p) + q
Where - p is the x value and q is the y value of turning point.
For graph 22, x = -1 and y = -3
Therefore, the equation is of the form
y = a(x + 1) - 3 (*)
We still need the value a, this can be obtained by using the y-intercept we are given.
We are told x = 0 when y = -2
Substitute this in (*) equation:
-2 = a(0+1) - 3
-2 = a - 3
a = 1
Therefore final equation is
y = 1(x +1) - 3
This should provide you with the train of thought of how the second question should also be tackled.
If unsure about why the equation
y = a(x + p) + q gives the vertex ask in comments I will respond
Answer:
yes, ordinary netizens have a right to do what they want or what opinion they want to say. Declaration of Indepence is not just for powerful people but also for ordinary netizens in order for them to spek the truth
Answer:
The coefficient is equal to ![4](https://tex.z-dn.net/?f=4)
Step-by-step explanation:
we have
![(-\frac{2}{3}x)(3y)(-2x)](https://tex.z-dn.net/?f=%28-%5Cfrac%7B2%7D%7B3%7Dx%29%283y%29%28-2x%29)
we know that
The coefficient is equal to
![(-\frac{2}{3})(3)(-2)=4](https://tex.z-dn.net/?f=%28-%5Cfrac%7B2%7D%7B3%7D%29%283%29%28-2%29%3D4)
so
![(-\frac{2}{3}x)(3y)(-2x)=4x^{2}y](https://tex.z-dn.net/?f=%28-%5Cfrac%7B2%7D%7B3%7Dx%29%283y%29%28-2x%29%3D4x%5E%7B2%7Dy)
Answer:
a
Step-by-step explanation:
because i got it right